Responses of blood vessels in the rabbit knee to acute joint inflammation. Issue 7 (July 1990) - Khoshbaten, A; Ferrell, W R
Abstract : These experiments examined the responses of articular blood vessels in the rabbit knee to induction of acute joint inflammation by intraarticular injection of 4% kaolin suspension. This produced an inflammatory response, which became evident about four hours after injection. Electrical stimulation of the nerve supply to the knee joint before induction of inflammation produced a biphasic response–an initial vasoconstriction during the stimulation phase followed by dilatation after stimulation stopped. These responses were followed up for eight hours and it was noted that the constrictor response became progressively greater, producing a further 19% decrease in blood flow during nerve stimulation about three hours after the injection of kaolin. The sensitivity of postjunctional alpha adrenoceptors, however, showed still greater increase in the inflamed joint as close intraarterial injection of 10(-6) M adrenaline produced an additional 30% reduction in blood flow four hours after kaolin injection compared with the control response. Possibly, the smaller enhancement of the constrictor response to nerve stimulation in the inflamed joint may reflect sensitisation of prejunctional alpha adrenoceptors in addition to the effects exerted on postjunctional alpha adrenoceptors by the inflammatory process. The dilator response also increased over eight hours, though this rise was less marked. These findings indicate that even over the limited time span of the experiments, significant alterations occurred in factors which influence the calibre of articular blood vessels.